KINETICS OF REDUCTIVE BULK DISSOLUTION OF LEPIDOCROCITE, FERRIHYDRITE, AND GOETHITE - Larsen O.; Postma D. (My University, 2001)
-The variation in Fe-oxide reactivity was investigated by studying the kinetics of bulk reductive dissolution of a suite of synthetic Fe-oxides in 10 mM ascorbic acid at pH 3. The Fe-oxides comprised three different ferrihydrites, five lepidocrocites, and a poorly crystalline goethite. During one of the reduction experiments, lepidocrocite crystals were subsampled and the change in crystal habit and size distribution was studied by transmission electron microscopy.The rate of complete dissolution was described by the function J/m0 = k'(m/m0)γ where J is the overall rate of dissolution (mol/s), m0 the initial amount of iron oxides, and m/m0 the undissolved mineral fraction. Rate laws were derived for the different iron oxides and showed a variation in initial rates of about two orders of magnitudes; 2-line ferrihydrites being most reactive with k' = 7.6-6.6 x 10-4 . s-1, whereas the initial rate for 6-line ferrihydrite is an order of magnitude lower 7.4 x 10-5 . s-1 and comparable to the quite homogeneous group of lepidocrocites (3.2-8.1 x 10-5 . s-1) with finally the initial rate of goethite being one order of magnitude lower again (5.4 x 10-6 . s-1). The transmission electron microscopy results for lepidocrocite showed strong etch-pitting of the crystals parallel to the c-axis resulting ultimately in disintegration of the crystals.For the different iron oxides, the initial rate was independent of the specific surface area, emphasizing the importance of the crystal structure for the dissolution rate. However, among the lepidocrocites the initial rate was proportional to the specific surface area.The exponent, γ was found to vary from a value near 1.0 for one of the 2-line ferrihydrites, two of the lepidocrocites and the goethite, to values close to 2.3 for the other 2-line ferrihydrite and the 6-line ferrihydrite. Thus, the largest variation in reduction rate during bulk dissolution is found for ferrihydrite. For the lepidocrocites, the preparations that predominantly consist of single domain crystals yielded γ-values near 1.4-1.6, whereas the multidomainic crystal preparations yielded values of 1.0-1.1. The parameter γ collects the effects of factors, such as the crystal geometry, the particle size distribution and the reactive site density. The relative importance of these factors was evaluated and particularly the particle size distribution appears to be of importance for iron oxides.